2016
DOI: 10.1038/srep20767
|View full text |Cite
|
Sign up to set email alerts
|

Building the Leviathan – Voluntary centralisation of punishment power sustains cooperation in humans

Abstract: The prevalence of cooperation among humans is puzzling because cooperators can be exploited by free riders. Peer punishment has been suggested as a solution to this puzzle, but cumulating evidence questions its robustness in sustaining cooperation. Amongst others, punishment fails when it is not powerful enough, or when it elicits counter-punishment. Existing research, however, has ignored that the distribution of punishment power can be the result of social interactions. We introduce a novel experiment in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 61 publications
3
57
1
Order By: Relevance
“…Empirically investigating the natural rise of governance could be regarded as investigating the creation of a leviathan29 in a laboratory. Recently, some research experimentally investigates how leviathans are built3031. This is an ambitious aim, and our idea is an important approach to investigate this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically investigating the natural rise of governance could be regarded as investigating the creation of a leviathan29 in a laboratory. Recently, some research experimentally investigates how leviathans are built3031. This is an ambitious aim, and our idea is an important approach to investigate this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals, after they see their group members' contributions, can execute a punishment that is costly to themselves, but more costly to the punished group member or members (13,19,(36)(37)(38)(39). Experiments have shown that individuals punish to motivate others to contribute more and that individuals respond to (the threat of) punishment by increasing subsequent contributions in public good provision (36)(37)(38)(39) and intergroup contests (13,18,19). Accordingly, Exp.…”
Section: Methods Summarymentioning
confidence: 99%
“…If, as we argue, HS is a prerequisite for punishment, then HS individuals potentially have access to an additional benefit, maintaining their HS position. Individuals prefer an environment where ''someone'' can punish (Gürerk, Irlenbusch, & Rockenbach, 2006) and will transfer power to individuals who are willing to punish noncooperation (Gross, Méder, Okamoto-Barth, & Riedl, 2016). Yet the benefits of HS, for example, a greater say in-group decision making, are often dependent on continuing to be a good social partner (von Rueden, Gurven, & Kaplan, 2008).…”
Section: Current Studies: Status and Observer Opinions Of Punishersmentioning
confidence: 99%